BLOOD GLUCOSE CONTROL AND BODY WEIGHT OF EXPERIMENTAL DIABETIC RATS CO-TREATED WITH MICRO NUTRIENTS (Journal of Biomedical Investigation, 2010)
Disturbance in blood glucose and fuel metabolism are hallmarks in diabetes mellitus, and antioxidants are believed to play a role in the control of this disturbances. In the current work, antioxidant such as manganese (10mg/kg/body weight), copper (2mg/kg/body weight) and zinc (15mg/kg/body weight) were supplemented in alloxan-induced diabetic rats for a period of 4 weeks. Initial and final Fasting Blood Glucose (FBG) of the rats was 77.29±8.65mg/dl and 75.00±7.22mg/dl in controls, 408.14±49.44mg/dl and 107.00±11.07mg/dl in diabetics treated not supplemented, and 448.14±43.1 8mg/dl and 83.14±5.45mg/dl in the diabetic treated and supplemented respectively. There was statistically significant difference in the final FBG concentration of supplemented and unsupplemented groups (p
Keywords: diabetes; Micro nutrients; Blood Glucose; Body Weight